AB1110 Are We Really Choosing Wisely? Use of Antinuclear Antibody Testing: A Single Center Based Experience. (10th June 2014) - Sheth, T.; Alcid, D.
Abstract : Background: In order to promote high-value-cost-conscious care, American College of Physician (ACP) & American College of Rheumatology (ACR) via the Choosing Wisely campaign furnished guidelines for use of ANA test and ANA subserologies (ANAS). 1 First, ANA should not be used as a screening test in patients presenting with fatigue, myalgia or nonspecific symptoms. Second, in a patient with an existing diagnosis of immunologic disease (ID), repeat testing of ANA is not indicated. Third, ANAS should not be ordered along with ANA testing, as ANAS are almost always negative if the ANA test is negative. Objectives: The study is aimed at determining the appropriateness of ANA testing in clinical setting. The objective is to identify patient or provider characteristics associated with ANA test results, to identify occasions where ANA testing does not reflect high-value, cost-conscious care, to identify economic burden associated with such testing and to identify how often a positive ANA results in to change in management. Methods: The study was conducted as a retrospective chart review. All patients who had ANA testing done at SPUH lab during 1/1/2012 to 12/31/2012 were selected. Inferential analysis by chi square test and multivariate logistic regression were done by SAS 9.0. Results: Total 475 patient encounters were found with mean age of 47.6 years and M:F ratio of 1:3. In 52 encounters (10.9%), ANA testing was done despite a known history of SLE. In 122 encounters (25.7%), ANA subserologies (ANAS) were ordered along with initial ANA testing. Out of 122 ANAS ordered, only 16 were positive (13.1% positivity rate); all of which had positive ANA test results. No patients with negative ANA testing had positive ANAS. Patients with female gender (OR 3.07, 95% CI 1.61-5.83), African American race (p 0.007) and those with known history of ID (OR 6.76, 95% CI 3.88-11.80) were more likely to have a positive ANA test result. Patients with male gender (OR 3.14, 95% CI 0.10-0.99), with known history of ID (p<0.001) and with a positive ANA test results (OR 3.25, 95% CI 2.05-5.16) were more likely to have positive ANAS. Age and location of patient did not have any association with ANA or ANAS test results. Rate of ANA positivity were significantly different in patient encounters amongst different specialties (p<0.001). ANA testing ordered in family medicine, pediatrics, gastroenterology and obstetrics encounters were more likely have negative results (OR 5.8, 10.2, 5.4 and 5.2 respectively) than one ordered by rheumatologist. Common indications for ordering ANA testing were monoarticular pain; 153 encounters (32.3%) were ordered for fatigue and malaise. Follow up visits were available in 338 patient encounters; of which on 7 occasions (2%) a positive ANA test result was followed by a change in diagnosis or treatment. Conclusions: A significant amount of ANA and ANAS testing done in clinical setting does not reflect high-value-cost-conscious care, and is associated with significant economic burden (>200, 000 USD/year). References: Yazdany J, Schmajuk G, Robbins M, et al. Choosing wisely: the American College of Rheumatology's Top 5 list of things physicians and patients should question. Arthritis care & research 2013;65:329-39. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.6027